A Simple, Mild and General Oxidation of Alcohols to Aldehydes or Ketones by SO2F2/K2CO3 Using DMSO as Solvent and Oxidant. Issue 10 (8th April 2019) - Zha, Gao‐Feng; Fang, Wan‐Yin; Leng, Jing; Qin, Hua‐Li
Abstract: A practical, general and mild oxidation of primary and secondary alcohols to carbonyl compounds proceeds in yields of up to 99% using SO2 F2 as electrophile in DMSO as both the oxidant and the solvent at ambient temperature. No moisture‐ and oxygen‐free conditions are required. Stoichiometric amount of inexpensive K2 CO3, which generates easy to separate by‐products, is used as the base. Thus, 5‐gram scale runs proceeded in nearly quantitative yields by a simple filtration as the work‐up. The use of a polar solvent such as DMSO, which usually promotes competing Pummerer rearrangement, is also noteworthy. This protocol is compatible with a variety of common N‐, O‐, and S‐functional groups on (hetero)arene, alkene and alkyne substrates (68 examples). The protocol was applied (99% yield) to a formal synthesis of the important cholesterol‐lowering drug Rosuvastatin. Abstract :